Enhancing ABK Program through Sewing and Design Skills Training at SLB Kemala Bhayangkari 2 Gresik, East Java - Hany Mustikasari; Siti Zahro; Tri Sagirani; Hedi Amelia Bella Cintya; Nugraha Nugraha; Faith Zefanya Farrel Go; Veronica Natasha; Rafindra Hyoga Pratama; Caisya Ibni Aulia Putri Reza (Smart Society, 2026)
In Indonesia, Sekolah Luar Biasa (SLB), or special schools, play an important role in preparing students with special needs for independent living through academic and vocational education. However, vocational fashion programs in many Indonesian SLBs remain constrained by limited practical facilities, inadequate equipment, and teachers' insufficient expertise in fashion design and garment production. This community service program aimed to strengthen teachers' instructional capacity and improve students' vocational life skills through sewing and fashion design training at SLB Kemala Bhayangkari 2 Gresik, East Java. The program adopted a Participatory Action Research (PAR) approach consisting of problem identification, collaborative planning, action, and evaluation. Data were collected through interviews, observations, practical assessments, and Kirkpatrick's evaluation model. The intervention included the provision of sewing technologies, training in machine operation and maintenance, color and pattern matching, sewing techniques, digital fashion design, and intensive mentoring in producing innovative fashion products. The program enhanced teachers' knowledge and practical competencies in fashion instruction while enabling students to progressively develop sewing and design skills through authentic production activities. Participants successfully produced a variety of fashion products, demonstrated improved technical competencies, and showed high enthusiasm and confidence throughout the training. These findings indicate that participatory vocational training combined with teacher capacity building provides an effective approach to strengthening vocational education for students with special needs and offers a practical model for improving employability-oriented learning in special schools.